Festival Resik Kali: Tubuh, Sungai, dan Spiritualitas: Praktik Ekologi Budaya dalam Proses Penciptaan Seni Festival Sungai “Resik Kali" - BAYUAJI, INDRATA NUR (GETER : Jurnal Seni Drama, Tari dan Musik, 2025)
The Resik Kali River Festival in Sukoharjo Village, Pacitan, is a cultural ecological practice that articulates the relationship between humans, nature, and spirituality through a series of rituals and art performances. This paper discusses the process of creating works in the Resik Kali Festival using an approach based on the methods of artistic creation, which include the stages of exploration, formulation of ideas, design of works, and artistic realization. Based on cultural ecology studies, the resik kali ritual is understood as a cultural strategy for caring for the ecological landscape and the identity of agrarian communities. Through dramaturgical analysis and the concept of the body as a medium of perception, this paper shows that this festival presents a participatory, dialogical, and ecological aesthetic experience. This study provides a conceptual contribution to art creation based on local wisdom, while also being relevant to the development of ecology-based artistic practices.